Research Methods as the Basis for Village Policy with an Evidence-Based Policy Approach - Mia Kusmiati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to formulate an integrative conceptual framework regarding the role of research methods in the formation of evidence-based village policy (EBP). The main focus is how qualitative, quantitative, and mixed methods research can be used to produce more inclusive, transparent, and accountable policies in the context of village development in Indonesia. This study uses a Systematic Literature Review (SLR) approach to scientific publications indexed by Scopus, Web of Science, and SINTA for the period 2015–2025. The literature synthesis shows that research methods play a crucial role in identifying village community needs, improving data quality, and strengthening accountability in the policy formulation process. The EBP approach has been shown to encourage citizen participation, increase transparency in village fund allocation, and minimize the dominance of short-term political interests. However, its implementation faces challenges such as limited capacity of village officials, inadequate data infrastructure, and low policy literacy at the local level. These findings are relevant for strengthening village capacity in managing development funds, developing policies based on the real needs of residents, and promoting social accountability. This article makes a new contribution to the local public policy literature by emphasizing the importance of research as an instrument for strengthening village governance.